Determinants of cash waqf giving in Malaysia: survey of selected works - Htay, Sheila Nu Nu; Mohamed, Mustafa Omar; Osman, Amirul Faiz (2012)
Cash waqf means a movable waqf that has been established with liquid money or in other word waqf by using a cash or money. Cash waqf carries several advantages which give great benefit to all parties, including the financial institutions, investor and societies. Typically, waqf usually focused on the land or building, but not many people or the donors have the asset to do waqf and therefore, cash waqf has come as a great alternative for individual who do not have an immovable asset but rather have movable assets i.e cash for donating. Thus, everyone can do a charity in form of cash waqf as long as they want to do it voluntary only for the sake of Allah s.w.t blessing. However, awareness and understanding of public about cash waqf is still low. The amount of cash waqf collected still at infancy level and do not generate sufficient funds of scale to carry out program with impact as compared with Singapore that has shown significant amount of collection though ruled by a secular government. By population, Malaysia is leading in term of number of population where the Muslim people consist of 61.3% from the 28.3 billions of population at 2010. Selangor state is the largest populations by 5.43 millions. Therefore, motivation of the public towards the contribution of cash waqf is something interesting to look at. Several potential determinants have been identified. There are i) religious satisfaction ii) literacy of waqf iii) trustworthiness iv) demographic factor v) efficient management and vi) tax incentive. The preliminary study is considered important to develop a clear understanding with regard to further development of cash waqf particularly in Malaysia.